THE ROLE OF ENTREPRENEURS AND COOPERATION COMPETITIVE TO ECONOMIC WELL-BEING AND DEVELOPMENT - Mangantar, Maryam . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstrack : Â The role of the entrepreneur is needed because of being similarly define the success of development. Many more role that an entrepreneur where the entrepreneur plays a role in increasing the economic activities, promote the nation's economy, improving the standard of living, reduce unemployment, tackle social tensions, and promote trade in both scale local, national and international. Actually, the role of entrepreneurs in promote world development have been conducted since their business activities. Businesses vying improve competitiveness by leveraging its competitive advantages of each, so that the entrepreneur had a hand in improving the well-being of society and have contributed also in the development of the world economy in general.This paper aims to examine theoretically about the role of entrepreneurship and cooperation- competitive to economic wellbeing and development, beginning with the understanding of entrepreneur, the role of entrepreneur in economic development, cooperation-competitive, entrepreneur and coopetition, entrepreneur and coopetition role in achieving social well-being and development. It is hoped that this paper can open the mind of thinking about coopetition and the role of entrepreneur in achieving the welfare of societyKeywords : Â Entrepreneurs, Cooperation, Economics, Development